Analysis of Heavy Mineral Sands by Quantitative X-Ray Powder Diffraction and Mineral Liberation Analyser û Implications for Process Control - S M. C Verryn; K Deysel (The Australasian Institute of Mining and Metallurgy, 2008)
In heavy mineral sands ilmenite, rutile and zircon are present in economic concentrations. These minerals are important sources of Fe, Ti and Zr for various industrial uses. The beach sands of northern KwaZulu-Natal, along the Zululand Indian Ocean coastline in South Africa, have been mined for 30 years. The various processes involved in mining and processing these minerals have been controlled by time-consuming and labour-intensive analysis methods which, in some cases, can be replaced by X-ray powder diffraction (XRD)-Rietveld analysis. Heavy minerals are concentrated in the plant to produce a heavy mineral concentrate (HMC). The heavy mineral extraction plant is controlled and informed of the proportions of minerals in the HMC according to their magnetic susceptibility. The different fractions are called magnetic, paramagnetic and non-magnetic fractions and quality control is based on their magnetic fraction weights combined with X-ray fluorescence (XRF) elemental analysis. This current quality control process is very time consuming and labour intensive. We have aimed to show that we can, by XRD, identify and quantify all the minerals in the HMC and also in the magnetic separations. These results are then compared with results obtained by Mineral Liberation Analyser (MLA) as well as with the results from the physical separation. It was possible to detect all minerals present in the material by XRD and use the Rietveld method for a full bulk mineral quantification. A maximum of 15 minerals can be included in the Rietveld refinement due to computational restraints. Major minerals detected are rutile, ilmenite and zircon and minor minerals are quartz, epidote, anatase, amphibole, monazite, magnetite, titanite and augite. The XRD and MLA results correlate relatively well and detailed results will be presented for HMC and magnetic fraction samples. Small differences were observed for some minerals due to the different ways in which minerals are detected or due to preparation methods within each method. Rutile seems to be more abundant in the XRD analysis and the detection of Anatase is possible by XRD, but not MLA. Leucoxene (consisting of mainly microcrystalline anatase, rutile and titanite is not detectable by XRD since it is not a mineral, but ilmenite alteration phases are observed instead. There is, however, a correlation between anatase, titanite and rutile detected by XRD and leucoxene analysed by MLA.